2021
DOI: 10.1002/tcr.202000184
|View full text |Cite
|
Sign up to set email alerts
|

Forging C‐SeCF3 Bonds with Trifluoromethyl Tolueneselenosulfonate under Visible‐Light

Abstract: This account highlights some of our recent work on photoinduced trifluoromethylselenolation reactions. This research program relies primarily on the design of a new key shelf‐stable selenating reagent that can be involved in various radical processes In particular, we demonstrated that trifluoromethylselenolation of arenes, alkenes, alkynes as well as aliphatic organic building blocks can be readily achieved under visible‐light irradiation. Mechanistic investigations based on 19F NMR studies, EPR spectroscopy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…Direct trifluoromethylselenolation reactions have been confirmed to be the most convenient methods for the formation of the C–SeCF 3 bond with diverse SeCF 3 reagents (e.g., Hg(SeCF 3 ) 2 , CuSeCF 3 , AgSeCF 3 , [(bpy)CuSeCF 3 ] 2 , [Me 4 N][SeCF 3 ], ClSeCF 3 , CF 3 SeSeCF 3 , TsSeCF 3 , ArCH 2 Se(O)CF 3 , and the others). 6f 9h i 11 62 Even so, the synthetic strategies to introduce a SeCF 3 group into organic compounds are still underdeveloped in comparison with the analogous trifluoromethylthiolation. This section summarizes the advances in photoinduced trifluoromethylselenolation, which has attracted increasing attention in recent years.…”
Section: Photocatalyzed Trifluoromethylselenolationmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct trifluoromethylselenolation reactions have been confirmed to be the most convenient methods for the formation of the C–SeCF 3 bond with diverse SeCF 3 reagents (e.g., Hg(SeCF 3 ) 2 , CuSeCF 3 , AgSeCF 3 , [(bpy)CuSeCF 3 ] 2 , [Me 4 N][SeCF 3 ], ClSeCF 3 , CF 3 SeSeCF 3 , TsSeCF 3 , ArCH 2 Se(O)CF 3 , and the others). 6f 9h i 11 62 Even so, the synthetic strategies to introduce a SeCF 3 group into organic compounds are still underdeveloped in comparison with the analogous trifluoromethylthiolation. This section summarizes the advances in photoinduced trifluoromethylselenolation, which has attracted increasing attention in recent years.…”
Section: Photocatalyzed Trifluoromethylselenolationmentioning
confidence: 99%
“…TsSeCF 3 was synthesized from the reaction of the in situ formed ClSeCF 3 with toluenesulfinate, and has been used to implement radical trifluoromethylselenolations under visible-light irradiation. 9h i In 2018, the same research group reported the first photocatalytic trifluoromethylselenolation of arenediazonium salts 276 with TsSeCF 3 in the presence of an organic photocatalyst at room temperature under white LED irradiation, furnishing the trifluoromethylselenolated arenes 277 (Scheme 55 ). 71 The reaction did not require any additive and showed good functional group tolerance.…”
Section: Photocatalyzed Trifluoromethylselenolationmentioning
confidence: 99%
“…44 In the past decade, trifluoromethyl tolueneselenosulfonate (TsSeCF 3 ) has been successfully employed as shelf stable reagent in trifluoromethylselenations taking place under photoredox catalyzed conditions. 45 Such derivative has been applied to the visible light driven synthesis of trifluoromethylselenolated arenes 6.1a−d and perfluoroalkylselenolated derivatives under metal-free conditions, by using Eosin Y as the photoredox catalyst (Scheme 6). The formation of the Ar−Se bond relies on the aryl radical addition onto TsSeCF 3 .…”
Section: Formation Of An Ar−se Bondmentioning
confidence: 99%
“…Interestingly, the reaction in the presence of halogen substituents gave the desired products in synthetically useful yields (15e-15h). To some extent, heterocyclic com- Very recently, we demonstrated that aryl sulfonyl fluorides could be obtained under visible-light metal-free procedures by using cyanoarenes as organophotocatalysts [35][36][37][38][39][40]. Indeed, the association of diazonium salts with DABSO in the presence or not of an external fluoride source (KHF 2 ) allows access to a wide variety of arylsulfonyl fluorides with moderate to very good yields (Scheme 12).…”
Section: Scheme 10 Fluorosulfonylation Of Aryldiazonium Saltsmentioning
confidence: 99%